A review on alternative methods to experimental animals in biological testing: Recent advancement and current strategies - Asif Husain; Dhanalekshmi U Meenakshi; Aftab Ahmad; Neelima Shrivastava; Shah A Khan (Journal of Pharmacy and Bioallied Sciences, 2023)
With an increase in the progression of research and development in the medical field, the experimental use of animals for the efficacy and safety testing of pharmaceuticals is on rise. Every year, millions of animals are used for experimental testing during which these suffer from pain and are then eventually sacrificed. Besides bioethical issues, animal experimentation is associated with many disadvantages like high cost, the requirement of skilled manpower, approval, and is time-consuming. Therefore, attempts have been made by researchers to design and develop a number of alternative methods that could bypass animal experiments. These methods not only give accurate results but can also save lives of millions of animals annually. Research techniques, including computer and robotics together with molecular biology techniques, are applied to discover new methods to replace animal testing. Several alternative methods are discussed in this review. Some of these methods can predict the behavior of drugs accurately and are as reliable as in-vivo animal models. Furthermore, these alternative methods offer a variety of advantages over experimental animals. However, there is still a great need to discover and develop new, accurate, and reliable methods to replace experimental animals.